The concept of ecosystem services: contributions, pitfalls and alternatives - Lele, Sharachchandra (Henry Stewart Talks, 2023)
Ecosystem services, Nature's contribution to people, Biodiversity conservation, Environment-society relationship, Dis-services, Economic valuation, Human well-being, Political economy